Managers As Educators In Business Organizations - Tan, Siew Tong (2000)
Malaysia's economic development to date has been supported principally by an abundant supply of natural resources. The wealth brought by these natural resources are certain to provide less opportunities for sustained ·development into the future given uncertain commodity prices, limited resources and slower growth in demand for these items. In the new millennium with. advancement in technology all over the world taking the centre stage, Malaysia must come to rely on the skill and ingenuity of its most valuable resource - people.